Source, distribution, and transformation of dissolved and particulate organic matters in Qinzhou Bay, Northern Beibu Gulf - Cai, Shangjun; Wang, Chao; Zhu, Qingmei; Lao, Qibin (Frontiers in Marine Science, 2023)
Both dissolved and particulate organic matters (DOM and POM) provide a reduced carbon pool of considerable size in coastal ecosystems, and the two are closely linked. Currently, however, the integrated study of DOM and POM remains limited, precluding a more in-depth understanding of their interaction in coastal regions. In April 2021, 13 surface water samples were collected from Qinzhou Bay, in the northern Beibu Gulf. The DOM samples were characterized using dissolved organic carbon (DOC) analysis and UV-visible and fluorescence spectroscopy techniques. We determined the POM for the particulate organic carbon and nitrogen (POC and PN) and also isotopic composition (δ13C and δ15N). The weak to negligible relationships found between the DOC, colored and fluorescent DOM, salinity, and chlorophyll a together suggested that DOM’s distribution in Qinzhou Bay is concurrently shaped by various processes, namely, hydrological and in situ biological processes. A high C/N ratio of 17, high POC/chlorophyll a ratio (253 ± 112), and depleted δ13C (−25.7 ± 1.6‰) confirmed that POM is highly degraded and originates mainly from allochthonous input, to which the terrigenous organic matter and freshwater phytoplankton each contributes 35%. The total organic carbon (TOC = DOC + POC) was positively correlated with the humic-like peak M, revealing the transformation of labile DOM and POM into recalcitrant DOM components. The in situ production efficiency of peak M in surface waters of Qinzhou Bay is one order of magnitude greater than that in inland waters or open oceans, indicating that not only temperature but also the activity of substrate is a key factor controlling the in situ production of recalcitrant DOM in Qinzhou Bay. High levels of TOC and humic-like fluorescent DOM suggest the mass coexistence of organic matter differing in its reactivity, highlighting the large potential for photochemical as well as microbial degradation in the future.